1969
DOI: 10.1192/bjp.115.519.199
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Personality Measures to the Alpha Rhythm of the Electroencephalogram

Abstract: Conventionalsaline pad electrodes were held to the scalp by a standard rubber head-cap. Bipolar recordings were made from electrode pairs C@-O@, 02-C4, 01-02 ‘¿ 99

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1970
1970
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Studies which have failed to support that hypothesis have been reported by Henry and Knott (1941), Claridge and Herrington (1963), Fenton and Scotton (1967), Gale, Coles, Kline, and Penfold (1971), Gale, Harpham, and Lucas (1972), and Winter, Broadhurst, and Glass (1972). The contrary hypothesis indicating higher levels of arousal for extraverts has been reported by McAdam and Orme (1954), Mundy-Castle (1955), and Broadhurst and Glass (1969). Some support indicating increased levels of cortical activity for introverts has been reported with the somatosensory evoked response (Shagass & Schwartz, 1965).…”
mentioning
confidence: 89%
“…Studies which have failed to support that hypothesis have been reported by Henry and Knott (1941), Claridge and Herrington (1963), Fenton and Scotton (1967), Gale, Coles, Kline, and Penfold (1971), Gale, Harpham, and Lucas (1972), and Winter, Broadhurst, and Glass (1972). The contrary hypothesis indicating higher levels of arousal for extraverts has been reported by McAdam and Orme (1954), Mundy-Castle (1955), and Broadhurst and Glass (1969). Some support indicating increased levels of cortical activity for introverts has been reported with the somatosensory evoked response (Shagass & Schwartz, 1965).…”
mentioning
confidence: 89%
“…(1983), Gale has come to the conclusion that the contradictions in the field can be resolved if some common sources of error are removed, particularly the variation in experimental conditions. These have ranged widely, from rest with closed eyes (Kondo, Bean, Travis & Knott, 1978) to potentially highly arousing tasks, such as mental arithmetic (Broadhurst & Glass, 1969). Gale argues that only conditions inducing intermediate arousal (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is a 24-item, Yes-?-No scale with higher scores suggestive of increasing extroversion. Although previous comparisons (2,31) with EEG records have been inconclusive, positive correlations were predicted based on Hypothesis 1. Test 3 was the Harvard Group Scale of Hypnotic Susceptibility (33).…”
Section: Subjectsmentioning
confidence: 72%